(untitled) (International Journal on Stereo & Immersive Media, 2022)
The commercial release of the Lumière Autochrome in 1907 made three-dimensional colour images appear in reach. The issues surrounding the viewing of autochromes seemed to be mitigated in the stereoscopic format, with stereo-autochromes branded a sensation in the photographic and popular press, compared to witchcraft in their combination of the stereoscopes’ sense of depth and relief with the autochrome’s full spectrum of colours. But over time, issues with the stereo-autochrome, ranging from ‘clumping’ to exposure times, fed into a rejection of the invention. This paper will draw on new research into the Victoria and Albert Museum’s collection of autochromes and related objects and ephemera.